Modernisasi Pondok Pesantren dalam Membangun Masyarakat Madani: (Studi Kasus di Pondok Pesantren Jami’atul Ulum Selogudig Wetan Pajarakan Probolinggo) - Herwati, Herwati; Maula, Ismatul (LP3M UNZAH GENGGONG, 2020)
ABSTRACT The modernization of pesantren is an approach for long-term solutions to various problems of Muslims today and in the future. Therefore, the modernization of pesantren is an important part of the birth of modern Islamic civilization. However, the results of the modernization of pesantren cannot be felt in just one or two days, but it requires a long process that will at least take about two generations. As a long process, pesantren modernization requires a clear and definite conceptual framework, so that it can lead to ideal pesantren. In the last decade, there has been a shift experienced by pondok pesantren. The Jami'atul Ulum Islamic Boarding School, which is more familiarly known as the JMU Pesantren, places a high priority on the quality of the students. The implementation of modernization of Islamic boarding schools in building civil society at the Jami'atul Ulum Islamic Boarding School, namely Kiai is no longer the only source of learning. The variety of new learning sources is getting higher, the dynamic of communication between the pesantren education system and other systems allows students to learn from many sources. Almost all pesantren provide formal education. There is a need for students to have diplomas and mastery of certain skills. There is a tendency for students to study science and technology. Learn with education costs and living costs in each month or quarter. Seeing the historical background and typology of pesantren, the characteristics and dynamics of the development of pesantren as a unique Islamic educational institution will directly or indirectly face the challenges of the times. The development of science has become an integral part in the efforts of Islamic boarding schools to respond to the challenges of the times. Keywords: Modernization of Islamic Boarding Schools, The Madani Society